Дифузiя частинок у двовимiрному випадковому полi швидкостi - Cherniak, O. M. (Publishing house "Academperiodika", 2019)
The two approaches to describe the diffusion process of test particles in a two-dimensional random velocity field are compared to each other: the method of decorrelation trajectories and the moment approximation. The frozen turbulence case is considered, because it is the most complicated test for statistical theories. The results of considered analytical approaches are verified by direct numerical simulation.